ANALISIS KESALAHAN BERBAHASA DALAM BIDANG MORFOLOGI PADA RUNNING TEXT DI TV ONE - Yuandi, Diky; Charlina, Charlina; Hermandra, Hermandra (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The study was titled Analysis of Error in morphology in the field Running Text on Tv One. This research aims to describe the form of language error in the field of morphology on running text on One TV. The method used is a descriptive analysis method with a qualitative approach. This research data is Running Text on Tv One which amounts to 206 data. The results of the study found (1) 196 affix disappearances, (2) 1 sound that is supposed to be yield but not to be dissolved, (3) 5 sound removals that should not be yield (4) 0 replacement morph (5) 4 of Morph ratings Incorrect affix, (7) 0 improper determination of the underlying form, (8) 0 incorrect affix placement on the merged word, (9) 0 repetition of an improper compound word. Key Words: Analysis Of Language Error, Morphology, Running Text, Tv One.